Assessment of Physico-Chemical Quality of Water in Aliero Dam (Kebbi State, Nigeria) - Abuh E, Godwin; Ansari, Abdullah Adil (International Journal of Climate Research, 2016)
Aleiro dam in Aleiro Local Government of Kebbi state (Nigeria) constructed in 2010 is not only used for irrigation purposes but also serves the ecological needs of the local communities. This study was carried out during the year 2010-11, in order to assess the physico-chemical quality of water in the dam reservoir. The water samples were collected for a period of 6 months (monthly basis), from the three marked channels and were subjected to physico-chemical analysis. The results indicated that water quality is up to the standards accepted by WHO and FAO. The water is suitable for irrigation as required values for the concentration of sodium, magnesium, calcium and other elements are within the approved range suggested by FAO.